ADULTERATION AND NEED OF SUBSTITUTION OF RAW MATERIALS – A REVIEW - Snehal, *Shahane; Anand, Tekade; Mukund, Dive; Kavita, Daulatkar (International Journal of Ayurveda and Pharma Research, 2018)
Experiencing challenges of modern medicine, globe is shifting towards the Ayurvedic theory of health management. In the treatment of disease use of medicine is practiced rampantly. This increased the demand of raw material exponentially. But, growth in production is still linear in nature. Fast depletion of resources is creating the major trouble. To meet the deficit, practices of adulteration and substitution are going on wildly. This adulteration and substitution became burning problem in industry threatening the integrity of Ayurveda. The deforestation, extinction or evolution of many species, insufficient knowledge, unauthenticated practices about identification, collection, storage and transport of raw material collectively resulted in adulteration. Strategic planning and integrated approach towards mass production, supply chain management, IEC, proper advocacy and knowledge sharing is needed to trim down the gravity of adulteration. “Prevention of Food Adulteration act 1954” describes technical definitions and guidelines for quality maintenance. Government is enforcing quality maintenance by implementation of “The Drug and Cosmetics Act 1940” For quality assurance, proper pharmacovigillance monitoring of raw materials and processes is very necessary. The concept of substitution is known in Ayurveda as it is enlightened prominently in Bhavprakash and Yogratnakar. However in scenario of crises, selection of substitute drugs may have upper edge over adulteration of the raw material. Scope of this article advocates that how adulteration and substitution are creating problems with respect to production of inferior quality medicines.